Analysis of Transitional Marker Usage in Expository Essays by First-Year Criminology and Hospitality Management Students at Saint Columban College - Villas, Carl Jahziel; Pandeling, Ruela Rose; Paet, Shequira; Gaan, Dayanara R.; Naparan, Genesis B. (Journal of Education and Learning Reviews, 2025)
Background and Aim: Coherence and cohesion are observed when ideas run smoothly with the use of correct transitional markers. This study examined the use of transitional markers in the essays of first-year Criminology and Hospitality and Management students at Saint Columban College. This study used the quantitative type of research with a purposive sampling technique where the researchers have the freedom to choose those who will be suitable to be part of the study. Analysis of 70 essays, written in response to a standardized prompt on procrastination, reveals limited usage and variety of transitional markers, with Criminology students using eight different markers 33 times, and Hospitality and Management students using nine markers 39 times. Transitional markers primarily served to introduce additional ideas, list ideas in time order, introduce opposing ideas, and conclude. However, Hospitality and Management students demonstrated more accurate usage, while Criminology students often misused markers, particularly "however." Both groups showed a notable absence of markers to introduce examples. These findings highlight a need for enhanced instruction in the effective use of transitional markers to improve academic writing skills. Materials and Methods: The researcher used a descriptive quantitative research design for this study, where the researcher focused mainly on the transitional markers used by college students in writing academic essays. According to Grove et al. (2013), descriptive designs “may be used to develop theory, identify problems with current practice, justify current practice, make judgments, or determine what others in a similar situation. Results: Findings revealed that both Criminology and Hospitality and Management first-year students have a limited range of transitional markers in their essays, with Criminology students using eight and Hospitality and Management students using nine. The primary functions of these markers were to introduce additional ideas, sequence thoughts, present contrasts, indicate results, provide examples, and conclude arguments. While Hospitality and Management students generally used transitional markers appropriately, Criminology students struggled, particularly with the contrastive marker "however." Based on these findings, a lesson plan focusing on the proper use and variety of transitional markers can be developed to enhance students’ coherence and cohesion in writing. Conclusion: The results of the study showed that students’ understanding of transitional markers was limited, and their knowledge scope was determined. The findings show that the absence of transitional markers and their improper application are.